The Protection Of Child Labour In India - Dilla Yuliani; Eka Kurniasari (Fakultas Hukum Universitas Syiah Kuala, 2018)
Child labour is a worldwide phenomenon but more focused is required on developing countries. India is a developing country with the second highest birth rate in the world after China. More than 200 million children in minimum age in the world that minors are forced into child labour and one of the countries with the largest child labour is India even in hazardous condition. As a federal state, government of India should uphold child rights in the society. The purposes of this thesis are to study and to understand the implementation of the law that ban children under the age of 18 to work; to scrutinize about the constraints faced by The Government of The Republic of India in addressing child labour; and to explain the protection on the rights of child in India and in Indonesia in comparison. This research uses normative research. Normative research is legal research theory, which identify and conceptualize the way the law as norms, rules, regulations including academic paper, research report, dictionary, etc. The result shows that India was among the first nations to sign the MoU with The International Programme on the Elimination of Child Labour (IPECL) to help in combating child labour. Unfortunately, the concerned authorities are unable to combat the rising cases of child labour because of varied reasons. UNICEF and BCC reports that poverty is the big cause of child labour in India. The girl child labourer is particularly alarming due to gender discrimination in large part of the society and also the complex relationship between social and child labour linked to the caste system. The caste system has been an enormous influence on the social and economic development of India. The Government of India has introduced numerous policy initiatives to try to reduce the effects of caste upon children’s life chances. It is suggested that in order to protect childrens in India, The Government of India is recommended to keep control and apply the law that ban children under minimum age to work and to prevent the scourge of child labour, the government of India should consistent and aware of the importances of respecting children’s rights.